Peningkatan Pemahaman Konsep Ipa Siswa Kelas V Pada Pokok Materi Gerak - Irdes Hidayana Siregar; Kasmawati Kasmawati (Gravity Journal, 2022)
This study aims to determine the increase in the ability to understand the concept of fifth grade students of SD Negeri No. 101560 Sihambeng Portibi District. To find out the increase in the ability to understand the concept of fifth grade students at SD Negeri No. 101560 Sihambeng Portibi District on Science Learning on motion material through the experimental method. The subjects were fifth grade students of SD Negeri No. 101560 Sihambeng Portibi District. This type of research is Classroom Action Research. The research design used is the Kemmis and Mc. Taggart which includes the stages of planning, implementing actions and observations, as well as reflection. The data collection instruments used were observation sheets, student activity scales, and worksheets. The data analysis technique used is descriptive qualitative and quantitative data analysis. Based on the results of data analysis in the first cycle of the first meeting, it showed an increase in students' understanding of science concepts. The results of the study were the application of learning with experimental methods, training students to be skilled in paying attention to experiments, conducting experiments or experiments, discussing among friends and expressing opinions between friends and teachers, presenting experimental results and asking questions between students and teachers. The application of experimental learning can improve students' understanding of science concepts in learning. The things that support the increase in student activity are teachers are more master of learning with experimental methods on motion material so that they can explain, direct, and guide students well.